EFFECT OF HYDROLYSIS REGIME ON STIFFNESS AND DEFORMATION AT BENDING OF RECYCLED MEDIUM-DENSITY FIBREBOARDS (rMDF) - Panchev, Christian; Savov, Viktor (Innovation in Woodworking Industry and Engineering design, 2023)
Recycling Medium-Density Fiberboard panels is a significant challenge and is not a widespread industry practice. Given the reduced costs, the methods for recycling this material with hydrothermal hydrolysis of the resins are more promising than those with acid hydrolysis. Despite the considerable amount of research on the topic, the effect of the hydrolysis regime on the stiffness and deformation at the bending load of recycled MDF panels (rMDF) remains limited. In the present work was conducted a study on the effect of hydrothermal hydrolysis regime, with a variation in temperature from 121°C (saturated steam pressure 0.2 MPa) to 134° (saturated steam pressure 0.3 MPa) and the hydrolysis time from 30 min to 60 min on the stiffness and deformation behaviour of rMDF. It was found that the stiffness of the panels was not significantly affected by the hydrolysis regime, but the rMDF had about ten per cent less stiffness than the control panel from natural fibres. It was determined that the optimal hydrolysis regime is at 121° and has a processing time of 30 minutes. Concerning the investigated rMDF characteristics, the panels are not recommended to be composed entirely of recycled fibres.